2023
DOI: 10.3390/analytica4020020
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles: A Didactic Step-by-Step of the Synthesis Using the Turkevich Method, Mechanisms, and Characterizations

Abstract: In this study, gold nanoparticles (AuNPs) were synthesized using the Turkevich method. This article explains the didactic step-by-step synthesis, showing pictures of the entire process, including a well-explained mechanism and characterization study. Synthesis involves the reduction of NaAuCl4 using sodium citrate at high temperatures (approximately 90 °C). The two main mechanisms used to explain AuNPs synthesis via the Turkevich method are also discussed. The first mechanism considers that a nanowire intermed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Previous studies have extensively documented the ability of citrate to reduce noble metal salts while undergoing oxidation (see Scheme ). The reduction process occurs through the transfer of electrons from the citrate ion to the metal ion, but this electron transfer is feasible only when citrate is present in its deprotonated form. In fact, it has been found that the reduction of gold ions only happens via the oxidation of fully deprotonated citrate (A 3– ) to the double deprotonated form (AH 2– ) as shown above (see also ref ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have extensively documented the ability of citrate to reduce noble metal salts while undergoing oxidation (see Scheme ). The reduction process occurs through the transfer of electrons from the citrate ion to the metal ion, but this electron transfer is feasible only when citrate is present in its deprotonated form. In fact, it has been found that the reduction of gold ions only happens via the oxidation of fully deprotonated citrate (A 3– ) to the double deprotonated form (AH 2– ) as shown above (see also ref ).…”
Section: Resultsmentioning
confidence: 99%
“… The reduction process occurs through the transfer of electrons from the citrate ion to the metal ion, but this electron transfer is feasible only when citrate is present in its deprotonated form. In fact, it has been found that the reduction of gold ions only happens via the oxidation of fully deprotonated citrate (A 3– ) to the double deprotonated form (AH 2– ) as shown above (see also ref ). The electronic state of the citrate ion is profoundly influenced by the pH of the solution, with higher pH values favoring a fully deprotonated state .…”
Section: Resultsmentioning
confidence: 99%
“…Electrostatic repulsion produced a dispersed solution with a red color. 45,46 The structure of dopamine consists of one –NH 2 and two –OH groups. These two important characteristics cause the gold nanoparticles to change from the dispersed to the aggregated state.…”
Section: Resultsmentioning
confidence: 99%
“…In a separate step, 420 µL NaAuCl 4 (0.125 M) was diluted in 94.6 mL of deionized water under agitation and heated to 90 • C. Subsequently, 5 mL sodium citrate (10 mg/mL) was quickly added whilst stirring and heating for 20 min. The color change from light yellow to red confirmed the formation of AuNPs [24]. The AuNPs were stored at 4 • C in the dark.…”
Section: Fabrication Of the Spe And Construction Of Immunosensormentioning
confidence: 94%